Kesejahteraan Subjektif Anak Indonesia: Eksplorasi Dimensi Emosional dan Kognitif - Borualogo, Ihsana Sabriani; Casas, Ferran (ANIMA Indonesian Psychological Journal, 2025)
Savahl et al. (2021) propose a quadripartite model for children's subjective well-being (SWB) that includes both: global (context-free items assessing overall well-being) and specific (domain-based items evaluating particular life aspects) cognitive components, as well as positive affect (PA) and negative affect (NA). The goal of this study is to test this model of SWB among Indonesian children using data from the third wave of the Children’s Worlds Survey. A representative sample of West Java children aged 10 and 12 years (N = 9,526). Data analysis involved confirmatory factor analysis (CFA). Results for a model with a second-order latent variable using the pooled sample displayed good fit indexes. The second-order analysis showed significant standardized regression weights of the SWB items of each latent variable, and of the first order latent variables on the second order latent variable as expected The high internal consistency of the CW-SWBS5, CW-DBSWBS, and CW-PNAS indicates that the quadripartite model of SWB is psychometrically robust among Indonesian children aged 10 and 12. However, the notably low factor loadings for items related to “satisfaction with the people children live with”—particularly when compared to higher-loading items such as “satisfaction with safety”—suggest a potential cultural divergence in how certain SWB domains are interpreted. Multigroup CFA showed that all statistics can be meaningfully compared between boys and girls and between 10 and 12-year-olds age groups. The findings of this study confirm this model can be used with Indonesian children and results offer valuable insights for parents, teachers, and policymakers aiming to develop evidence-based interventions that support child well-being across cognitive and emotional domains.